Family group, possibly Kutchin Indians, outside of tent dwelling, Fortymile, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Northern Tlingit Indians. Caption on image: "An Indian family at Forty Mile"